OPTIMIZATION OF COLOPROCTOLOGY PATIENT PATHWAYS IN THE CONTEXT OF UZBEKISTAN’S DIGITAL HEALTH TRANSFORMATION (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
The rising incidence of colorectal cancer and other coloproctological conditions necessitates a revision of care delivery models. In Uzbekistan, fragmentation between outpatient and inpatient services continues to undermine the efficiency of diagnosis, treatment, and follow-up care. This article presents a conceptual framework for an integrated model of coloproctology care, developed with consideration of both international best practices and the national healthcare context. A central element of the model is digital patient routing, supported by a unified electronic medical record, remote monitoring tools, and multidisciplinary coordination. The proposed system is expected to streamline the patient journey, reduce delays in diagnosis and treatment, lower the share of emergency interventions and readmissions, and provide a robust data infrastructure for quality management in coloproctology.